Sorangicin A Is Active against Chlamydia in Cell Culture, Explanted Fallopian Tubes, and Topical In Vivo Treatment - Simon Graspeuntner; Katharina Koethke; Celeste Scholz; Lea Semmler; Mariia Lupatsii; Laura Kirchhoff; Jennifer Herrmann; Katharina Rox; Kathrin Wittstein; Nadja Käding; Lars C. Hanker; Marc Stadler; et al. (MDPI AG, 2023)
Current treatment of Chlamydia trachomatis using doxycycline and azithromycin introduces detrimental side effects on the host's microbiota. As a potential alternative treatment, the myxobacterial natural product sorangicin A (SorA) blocks the bacterial RNA polymerase. In this study we analyzed the effectiveness of SorA against C. trachomatis in cell culture, and explanted fallopian tubes and systemic and local treatment in mice, providing also pharmacokinetic data on SorA. Potential side effects of SorA on the vaginal and gut microbiome were assessed in mice and against human-derived Lactobacillus species. SorA showed minimal inhibitory concentrations of 80 ng/mL (normoxia) to 120 ng/mL (hypoxia) against C. trachomatis in vitro and was eradicating C. trachomatis at a concentration of 1 µg/mL from fallopian tubes. In vivo, SorA reduced chlamydial shedding by more than 100-fold within the first days of infection by topical application corresponding with vaginal detection of SorA only upon topical treatment, but not after systemic application. SorA changed gut microbial composition during intraperitoneal application only and did neither alter the vaginal microbiota in mice nor affect growth of human-derived lactobacilli. Additional dose escalations and/or pharmaceutical modifications will be needed to optimize application of SorA and to reach sufficient anti-chlamydial activity in vivo.